L’américanisation d’un intellectuel français : le cas d’Yves Simon (1903-1961) - Florian Michel (Transatlantica)
In 1938, Yves Simon, who taught philosophy at the Paris and Lille Catholic Institutes, received an invitation to teach at Notre Dame University in Indiana. From then on, a process of americanization developed involving his family and professional connections, whose consequences transformed both religious and intellectual history. Well integrated into the American society, Yves Simon became a US citizen in 1946 and actively participated in intellectual exchanges between the two cultures.